Regional Information Tools for Providing Development of Regional Socio-Economic System. (Economics and region, 2019)
The article focuses on the analysis of information tools system for ensuring socio-economic activity of the regions in Ukraine. The author proposes to understand the means of displaying real economic phenomena and economic interests, analyzing, assessing and making managerial decisions that have the potential to form new knowledge about the state of economic systems as information tools for the development of regional socioeconomic systems. The paper considers two different levels of social needs in regional information tools. The factors that determine the composition of user needs as to the indicated tools in the region's space are indicated; it is proposed to distinguish three users groups of information tools for providing regions’ economic security by applying distinctive feature of economic interest nature. The creation of information systems as information tools for regional systems economic-innovative development and ensuring economic security of the region is considered. The paper deals with such subsystems of information tools for regional development as analytical, internal monitoring and external monitoring.
Keywords: information tools; information system; economic security of the region; regional space